Assessing the Impact of Dairy Policies on Farm-Level Profits in Dairy Farms in Bangladesh: Benchmarking for Rural Livelihoods Improvement Policy - Uddin, M.M.; Sultana, M.N.; Bruermer, B.; Peters, K.J. (Journal of Reviews on Global Economics, 2012)
Abstract: The objective of this study was to benchmark the set of dairy supporting policies on farm level profit in small-scale dairy farmers and also analyse how improved dairy support services and adoption of technologies enhance rural livelihoods. This study applies the International Farm Comparison Network (IFCN) method. The data were analysed by utilizing the extended version of TIPI-CAL (Technology Impact Policy Impact Calculations) model (TIPI-CAL software version 5.1). The improved dairy support services: marketing access (IM-MKS), veterinary services (IM-VHS), feeding and nutritional services (IM-FNS), community based fodder production system (CB-FPS), national breeding programme (NL-BRP) showed the highest impact on milk yield, entrepreneur's profit and household income in all three production systems compared with its base line farms. The extensive and traditional systems were responding more to the proposed policies to increase the entrepreneur's profits compared with intensive production systems. Adoption of policy increases the daily household income above the absolute poverty line (1US$/day). This study results could be useful for prioritizing the policies on delivery of support services and technology and are expected to be helpful as a benchmark to implement the 'draft policy proposal' by the Ministry of Fisheries and Livestock (MOFL) in Bangladesh.